Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.5194/egusphere-egu2020-3943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiband (X, C, L) radar amplitude analysis for a mixed sand- and gravel-bed river in the eastern central Andes

Abstract: <p>Synthetic Aperture Radar (SAR) amplitude measurements from spaceborne sensors are sensitive to surface roughness conditions near their radar wavelength. These data can be exploited to measure gravel-to-sand transitions and downstream gradients in grain size related to geomorphic setting in tectonically active high mountain environments at large spatial scales. The bedload of mixed sand- and gravel-bed rivers can be considered mixed smooth (compacted sand) and rough (gravel) surfaces. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…These include steep topographic gradients, pervasively fractured bedrock in the steep hanging walls of basin‐bounding faults, frequent rainstorm events during summer, and ongoing tectonic activity. In addition, the strongly deformed and cataclasized Proterozoic phyllites of the Puncoviscana Formation predispose this region to debris flows (e.g., Garcia et al., 2019; Olen & Bookhagen, 2018; Purinton & Bookhagen, 2020; Tofelde et al., 2017). Sudden rupture events along basin‐bounding faults in this environment can also trigger rockfalls and landslides (Strecker & Marrett, 1999) or generate pervasive rock fractures that supply large volumes of unconsolidated material to debris flows, similar to tectonically active high‐relief environments elsewhere (e.g., Tang et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include steep topographic gradients, pervasively fractured bedrock in the steep hanging walls of basin‐bounding faults, frequent rainstorm events during summer, and ongoing tectonic activity. In addition, the strongly deformed and cataclasized Proterozoic phyllites of the Puncoviscana Formation predispose this region to debris flows (e.g., Garcia et al., 2019; Olen & Bookhagen, 2018; Purinton & Bookhagen, 2020; Tofelde et al., 2017). Sudden rupture events along basin‐bounding faults in this environment can also trigger rockfalls and landslides (Strecker & Marrett, 1999) or generate pervasive rock fractures that supply large volumes of unconsolidated material to debris flows, similar to tectonically active high‐relief environments elsewhere (e.g., Tang et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous regional studies have revealed high erosion rates based on 10 Be cosmogenic nuclide dating of sands from the Río Capilla subcatchments (Bookhagen & Strecker, 2012; Tofelde et al., 2017). In addition, grain‐size measurements indicate a significant increase in pebble sizes downstream of the confluence of the Río Capilla with the Río Toro mainstem (Purinton & Bookhagen, 2020, 2021). These observations are consistent with the distribution of channels with high debris‐flow similarity, which are widespread within the Río Capilla catchment (Figure 14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary hydro‐meteorologic conditions are characterized by a wet and dry season (coinciding with the South American Summer Monsoon) with frequent, high‐intensity rainfall events and recent trends of increasing rainfall and river discharge related to climate change (Castino et al., 2016a, 2016b, 2017, 2020). Finally, high rates of bedload transport have been observed along the Río Toro (Purinton & Bookhagen, 2018), and associated spaceborne radar measurements of this bedload material indicate the wide range and variability of grain size (Purinton & Bookhagen, 2020), along with the seasonal motion of this material (Olen & Bookhagen, 2020).…”
Section: Study Areamentioning
confidence: 99%
“…Satellite data, despite their low spatial resolution (metres per pixel), have been used in sub‐pixel methods to study landscape units with characteristic dimensions below 100 m, or even below 10 m (Busetto et al, 2008; Verhoeye & De Wulf, 2002). A recent study by Purinton & Bookhagen (2020) showed that radar amplitudes collected by several satellites, with different wavelength and resolution, have the potential to identify sediment size in mixed sand‐ and gravel‐bed rivers.…”
Section: Introductionmentioning
confidence: 99%